Особенности конструктивно-технологических решений приемной системы малых радиотелескопов - Глушеченко, Э.Н.; Пилипенко, А.М.; Слонин, Э.В.; Сундучков, И.К.; Чмиль, В.В. (Технология и конструирование в электронной аппаратуре, 2016)
Описаны новые технологические решения и конструктивные подходы для проектирования радиометрической приемной системы для антенн малого диаметра. Сформулированы проблемы, которые необходимо преодолеть при реализации подобных систем. Подробно рассмотрены конкретные решения, которые прошли апробацию и предлагаются для реализации систем такого класса. Наведено нові технологічні рішення та конструктивні підходи щодо проектування радіометричної приймальної системи радіоастрономії для антен малого діаметру. Сформульовано проблеми, які необхідно подолати при реалізації подібних систем. Детально розглянуто конкретні рішення, що пройшли апробацію та пропонуються для реалізації систем такого класу. The article presents new technological solutions and structural approaches for design of radiometric receiving systems for small diameter antennas. Problems which need to be dealt with in the process of realization of such systems are formulated. All of the considered problems, both structural and technological, encountered when creating radiometric receiving systems for small diameter antennas, were not only tested on the mockups, but also successfully implemented in three sets of radiometric systems of modern radio astronomy facilities. In addition, the described approach to solving these problems is recommended for the wide application by the international VLBI service.